Management of Self Concept in Nursing for Quality of Life and Dilemma Ethics among Cancer Patients - Pujiastuti, Rr. Sri Endang (KnE Life Sciences, 2019)
Biopsychosocial changes in cancer patients affect compliance psychosocial needs. Various efforts made to meet the patient’s needs can maintain integrity and achieve balance. The purpose of this study was to explore the fulfillment of psychosocial needs with a self concept for cancer patients. The method of this study is qualitative design descriptive phenomenology. The participants were eight breast cancer patients who underwent mastectomy and chemotherapy. Data retrieval was done by interview. Data analysis was carried out using the stages of analysis according to Colaizzi. Results: The research has five themes, namely (1) feelings when diagnosed with disease affect feelings in undergoing treatment, (2) physical symptoms affect the self concept, social aspects, and spiritual aspects, (3) self-acceptance reaction to cancer conditions determine the coping strategy undertaken, (4) the needs of breast cancer patients consist of physical, psychological, social, and spiritual needs, and (5) the needs of cancer patients can be met physically, psychologically, socially, and spiritually. Based on the results of the study. It can be concluded that self concept from the five main themes and the physical symptoms in cancer patients affects the needs and fulfillment of physical, psychological, social, and spiritual needs. This study recommends the need for a special nursing assessment format for psychosocial needs and how to fulfill them.